2009
DOI: 10.1073/pnas.0900304106
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related similarities and differences in the neural correlates of beauty

Abstract: The capacity to appreciate beauty is one of our species' most remarkable traits. Although knowledge about its neural correlates is growing, little is known about any gender-related differences. We have explored possible differences between men and women's neural correlates of aesthetic preference. We have used magnetoencephalography to record the brain activity of 10 male and 10 female participants while they decided whether or not they considered examples of artistic and natural visual stimuli to be beautiful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
120
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 65 publications
12
120
0
1
Order By: Relevance
“…Relative to this, considerable evidence has been accumulated supporting the notion that both facial and bodily physical attractiveness are 'health certifications' and thus represent honest signals of phenotypic and genetic quality (Grammer et al, 2003). From this perspective, the esthetic evaluation of human body, and in particular of the body of individuals of the opposite gender (in heterosexual individuals), has a particular importance for our survival, being strictly connected with reproductive behavior (Cela-Conde et al, 2009;Dixson, A., Dixson, B., & Anderson, 2005). Accordingly, previous studies have shown greater brain responses to opposite than same-gender bodies involving in particular those electro- (Hietanen & Nummenmaa, 2011) or magneto-encephalographic (Costa, Brawn, & Birbaumer, 2003) components related to perceptual processing of the stimuli in the occipito-temporal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to this, considerable evidence has been accumulated supporting the notion that both facial and bodily physical attractiveness are 'health certifications' and thus represent honest signals of phenotypic and genetic quality (Grammer et al, 2003). From this perspective, the esthetic evaluation of human body, and in particular of the body of individuals of the opposite gender (in heterosexual individuals), has a particular importance for our survival, being strictly connected with reproductive behavior (Cela-Conde et al, 2009;Dixson, A., Dixson, B., & Anderson, 2005). Accordingly, previous studies have shown greater brain responses to opposite than same-gender bodies involving in particular those electro- (Hietanen & Nummenmaa, 2011) or magneto-encephalographic (Costa, Brawn, & Birbaumer, 2003) components related to perceptual processing of the stimuli in the occipito-temporal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral angular gyrus (AG) activity also has demonstrated to register greater activation during beautiful stimuli processing (Cela-Conde et al 2009) probably as support for enhancement of spatial processing strategies while viewing images by each subject, such as forms and color (Bartels and Zeki 2000) or symmetry and complexity (Jacobsen et al 2005). Similarly, it has also been reported increased auditory cortex activity during aesthetic judgment of music (Koelsch et al 2006).…”
Section: Sensory Regionsmentioning
confidence: 92%
“…And third, art making and appreciation serves an important ritualistic function that enhances social cohesion. Space limitations do not allow an adequate consideration of evolutionary perspectives on beauty and art (see Brown & Dissanayake, 2009;Cela-Conde et al, 2009;Dissanayake, 2008;Zaidel, 2005;Grammer, Fink, Moller, & Thornhill, 2003;PentonVoak et al, 2001;Etcoff, 1999;Rentschler, Jüttner, Unzicker, & Landis, 1999;Thornhill & Gangestad, 1999;Zahavi & Zahavi, 1997;Symons, 1979 for relevant discussions). Ultimately, evolutionary and cognitive neuroscience approaches to aesthetics are likely to converge in informative ways.…”
Section: Experimental Neuroaesthetics Frameworkmentioning
confidence: 99%